The White House staff : inside the West Wing and beyond - Patterson, Bradley H. (Bradley Hawkes), 1921-2020 (Brookings Institution Press, 2000)
" ... Bradley H. Patterson Jr. ... takes us inside the closely guarded turf of the White House. In a straightforward narrative free of partisan or personal agendas, Patterson provides an encyclopedic description of the contemporary White House staff and its operations."--Inside jacket